Current Biotechnological Advances and Challenges in Culture and Transplantation of Spermatogonial Stem Cells in Animals - Binsila, Balakrishnan; Tomy Tomcy, Anjilikal; Krishnappa, Balaganur; Arangasamy, Arunachalam; Ramachandran, Natesan; Selvaraju, Sellappan (The Indian Journal of Animal Reproduction, 2025)
The spermatogonial stem cells (SSCs) are unique stem cells of the adult body having the power of self-renewal and differ entiation into spermatozoa. Due to their distinct advantages over other stem cell types, the field of cell based regenerative  medicine is exploring the potential of SSCs for its various applications in biotechnology and animal reproduction. Here  we discuss about several approaches for SSC isolation, enrichment and characterization. Given the low percentage of  SSCs in the testis, it is difficult to obtain an enriched population of SSC for further research. Differentiation and apoptosis  over time is another challenge in establishing a long term SSC culture system. Hence, optimization of the culture media  and culture conditions along with cryopreservation is a prerequisite for the downstream application of SSC technology  in livestock. Although several markers have been identified for SSCs in animals, an appropriate species specific marker is  still lacking. Suitable recipients for SSC transplantation are generated through surrogate sire technology in livestock. SSC  transplantation has been experimentally successful in numerous livestock species with donor derived spermatogenesis  and production of offspring. Such advancement coupled with genome editing may open new avenues for augmenting  livestock production in near future. We emphasize that a deeper understanding of the SSCs characteristics and the fac tors that influence their differentiation and stemness is essential for the wider application of SSC technology in animals.
Keywords: spermatogonial stem cell; isolation; enrichment; culture; transplantation